The Depth Analysis Of Arabic Language Materials At MTs Al-Futuhiyyah Bumen Wonosobo - Amalia, Lia; Maulida Ma’rufa, Sulton Fajar Ayu; Nada, Royani Qothrun; Sahal Mahfudz, Ahmad; Sunati, Nur Ahya; Sholihah, Adellia Alfiani (DAS Institute, 2023)
Teaching materials are an essential tool in learning because, with teaching materials, the implementation of education can run smoothly and in a focused manner. This research will analyze the depth of class VIII Arabic language material at MTs Al-Futuhiyyah Bumen Wonosobo. This research aims to 1) find out whether the subject matter presented is relevant to the curriculum, competency standards, and basic competencies that support language skills, namely writing, reading, speaking, and listening, 2) find out the standards for presenting written material in each subject matter, 3) knowing the advantages and disadvantages of the textbooks studied. This research uses qualitative research in the form of field research. By using primary data sources directly through books, journals, etc., and secondary data, namely indirect sources through observation, interviews, and documentation. So the data collection technique uses the results of the interview. The data analysis used is Huberman miles analysis.